Transitioning from Conflict: India-Sri Lanka Relations in the Aftermath of Turmoil - Ahmad Sheikh, Javaid (International Journal of Psychosocial Rehabilitation, 2019)
In the world of international relations, India's foreign policy toward Sri Lanka has been a contentious and significant issue. This abstract offers a succinct summary of the complex forces that have influenced and still affect India's strategy toward its southern neighbor, Sri Lanka. The development of this bilateral relationship has been significantly influenced by the historical backdrop of their connections, geopolitical considerations, economic interests, security concerns, and cultural linkages. This study examines how India-Sri Lanka ties have developed through time, highlighting significant historical turning points and the underlying forces that have influenced India's foreign policy choices. It explores the many opportunities and challenges that have emerged, such as economic cooperation, maritime disputes, ethnic conflict, and the growing influence of external powers.